Integrating High-Resolution Mapping and Multiscale Fragmentation to Assess Ecosystem Patterns in Shola Forest - Grassland Mosaics of Western Ghats Biodiversity Hotspot - C. Sudhakar Reddy; Aswany S. Kumar; N. Nitish Sri Surya; M. A. Devika; K. H. Amitha Bachan (Journal of the Indian Society of Remote Sensing, 2026)

OGTCN-E-MGO: an optimized deep learning framework for EEG-based schizophrenia detection - V. Milner Paul; Adarsh V. Parekkattil; Devika S. Kumar; Jijo Francis; Lal D. V. Nair; T. Jarin; Loitongbam Surajkumar Singh; Shuma Adhikari (Physical and Engineering Sciences in Medicine, 2026)

Integrated subsurface drip fertigation and residue management enhance maize resource-use efficiency in semi-arid agro-ecosystems - Arjun Singh; Anchal Dass; S. Sudhishri; V.K. Singh; Prameela Krishnan; Pravin K. Upadhyay; K. Shekhawat; R.N. Sahoo; S.S. Rathore; Ayekpam Dollina Devi; A.R. Devika (Field Crops Research, 2026)

Determination of phytocompounds and their role in inhibition of efflux pump-related resistance in Pseudomonas aeruginosa PA7 - Jayavigneshwar Natarajan; Shubhi Singh; Sorna Lakshmi S; Ishaan Ramachandran; Devika Sharma; Bhuvaneshwaran R; Priya Swaminathan (Folia Microbiologica, 2026)

Metabolic Insights into Drug Absorption: Unveiling Piperine's Transformative Bioenhancing Potential - Devika Tripathi; Vivek Kumar Gupta; Prashant Pandey; P. S. Rajinikanth (Pharmaceutical Research, 2025)

Impact of terrestrial organic matter input on distributions of hydroxylated isoprenoidal GDGTs in marine sediments: Implications for OH-isoGDGT-based temperature proxies - Devika Varma; Yord W. Yedema; Francien Peterse; Gert-Jan Reichart; Jaap S. Sinninghe Damsté; Stefan Schouten (Organic Geochemistry, 2025)

Miconia crenata invasion in different ecosystems of Thiruvananthapuram district and the development of a potential management approach - Devika S. Kumar; M. Rajendraprasad (Journal for Nature Conservation, 2025)

Corrigendum to “Reconstructing the geological and geomorphological history of Morella Crater, Mars” [Geomorphology 479 (2025) 109740] - P.B. Hiral; S. Anbazhagan; S. Rahul; Shania James; T. Sadeeda Marjan; Devika Padmakumar; J. Aswathi; K.S. Sharini; Alka Rani; K.S. Sajinkumar; Rajiv R. Bharti; V.J. Rajesh; et al. (Geomorphology, 2025)

Reconstructing the geological and geomorphological history of Morella Crater, Mars - P.B. Hiral; S. Anbazhagan; S. Rahul; Shania James; T. Sadeeda Marjan; Devika Padmakumar; J. Aswathi; K.S. Sharini; Alka Rani; K.S. Sajinkumar; Rajiv R. Bharti; V.J. Rajesh; et al. (Geomorphology, 2025)

Serpentinisation of dolostone and chrysotile mineralisation in Vempalle Formation, Cuddapah Basin, India - P Megha Chandran; D S Devika; M S Pandian (Journal of Earth System Science, 2025)

Deciphering Regulatory Role of Melatonin in Foliar Nastic Movements of Portulaca oleracea: Visual Insights from Histology and Anatomy - Soundaryaa Bargunam; Riyan Roy; S. H. Amisha; Devika Shetty; Vidhu Sankar Babu (Journal of Plant Growth Regulation, 2025)
Plant nastic movements exhibit unique behavioural patterns that synchronize with external cues. Given that the foliar nastic motions of Portulaca species are solely circadian, it is intriguing to investigate whether and how melatonin governs these movements. Analysis of histological traits concurrent with anatomical traits such as stomatal behaviour provides visual data on the plant species' gnosophysiology, offering clues and validation of the influence of multiple external stimuli on hydraulic forces that in turn alter turgor pressure. The current study aims to elucidate how exogenous melatonin modulates foliar nastic movements in Portulaca oleracea . Our findings indicate that melatonin functions as an intracellular hydraulic flux controller, influencing idioblast and crystal densities, as well as stomatal behaviour. Timepoint studies at specific Zeitgebers reveal that abiotic variables such as light and temperature can influence the endogenous melatonin concentration of P. oleracea. Therefore, this hormone potentially serves as an additional internal regulator of turgor pressure, influenced by both light and temperature. Thus, melatonin plays a crucial role in shaping the characteristic foliar nastic movements observed in P. oleracea , inherently tied to the circadian rhythm. Further investigation into idioblast and crystal torques, along with their angular momentum, is warranted to calculate the hydraulic forces at work in the leaf lamina. Thus the study underscores the multifaceted role of melatonin in navigating nastic movement processes through turgor pressure alterations brought about by intracellular depositions. The study in future could unravel melatonin's pleiotropic actions and the underlying mechanisms of foliar idiosyncratic nastic motions in other plant species as well. Moreover, both histology and anatomy play vital roles in the present study as it has provided visual evidence of the underlying mechanisms of foliar nastic movements in P. oleracea . Graphical Abstract

Human biomonitoring health-based guidance values: A case study of the HB2GV Dashboard and DEHP - Kristin Macey; Rosa Lange; Petra Apel; Devika Poddalgoda; Antonia M. Calafat; Marike Kolossa-Gehring; Judy S. LaKind; Lisa Jo Melnyk; Shoji F. Nakayama; Annie St-Amand; Tyler Pollock (International Journal of Hygiene and Environmental Health, 2025)

Source of ore constituents for the hydrothermal barite mineralization in Vempalle Formation, Cuddapah Basin, India: Constraints from petrography, geochemistry and sulphur isotope composition - D S Devika; P Megha Chandran; M S Pandian (Journal of Earth System Science, 2024)

Inflammation and aging-related disease: A transdisciplinary inflammaging framework - Brian J. Andonian; Joseph A. Hippensteel; Katrina Abuabara; Eileen M. Boyle; James F. Colbert; Michael J. Devinney; Adam S. Faye; Bharati Kochar; Jiha Lee; Rachel Litke; Devika Nair; Sebastian E. Sattui; et al. (GeroScience, 2024)

Cubosomes as versatile lipid nanocarriers for neurological disorder therapeutics: a comprehensive review - Safa A Vahab; Ayushi Nair; Devika Raj; Akhil G P; Sreelakshmi P P; Vrinda S Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Evaluating isoprenoidal hydroxylated GDGT-based temperature proxies in surface sediments from the global ocean - Devika Varma; Ellen C. Hopmans; Zoë R. van Kemenade; Stephanie Kusch; Sonja Berg; Nicole J. Bale; Francesca Sangiorgi; Gert-Jan Reichart; Jaap S. Sinninghe Damsté; Stefan Schouten (Geochimica et Cosmochimica Acta, 2024)

The Luna structure, India: A probable impact crater formed by an iron bolide - K.S. Sajinkumar; S. James; G.K. Indu; Saranya R. Chandran; Devika Padmakumar; J. Aswathi; S. Keerthy; M.N. Praveen; N. Sorcar; J.K. Tomson; Anil Chavan; Subhash Bhandari; et al. (Planetary and Space Science, 2024)

Lignocellulosic magnetic biochar with multiple functionality; A green chelating system for water purification - Bency John; Devika Krishnan; S. Sumayya; Alfy George; Harsha Mahadevan; K. Anoop Krishnan (Journal of Environmental Chemical Engineering, 2023)

Geologic, geomorphic, tectonic, and paleoclimatic controls on the distribution and preservation of Chicxulub distal ejecta: A global perspective - S. James; Saranya R. Chandran; J. Aswathi; Devika Padmakumar; K.S. Sajinkumar (Earth-Science Reviews, 2023)

Impact of COVID-19 Lockdown on Ambient Air Quality in the Southwest Coastal Urban Regions of India - George Thomas; Jobin Thomas; R. S. Devika; Anju Krishnan; Anju V. Mathew; Amrutha J. Nair (Aerosol Science and Engineering, 2023)

A compendium of the best-preserved terrestrial hypervelocity impact crater in a basaltic terrain: The Lonar, India - Saranya R. Chandran; S. James; J. Aswathi; Devika Padmakumar; T. Sadeeda Marjan; R.B. Binoj Kumar; Anil Chavan; Subhash Bhandari; K.S. Sajinkumar (Earth-Science Reviews, 2023)

Reply to the ‘Critical comment on Aneeshkumar, V. et al., 2022, Lithos 426–427, 106779, Meteorite impact at Ramgarh, India: Petrographic and geochemical evidence, and new geochronological insights’ by W.U. , Lithos - V. Aneeshkumar; Saranya R. Chandran; S. James; M. Santosh; Devika Padmakumar; J. Aswathi; S. Keerthy; Y. Anilkumar; M.N. Praveen; M. Satyanarayanan; K.S. Sajinkumar (Lithos, 2023)

Biorecognition elements appended gold nanoparticle biosensors for the detection of food-borne pathogens - A review - Sandhya Sadanandan; Meenakshi V. S; Keerthana Ramkumar; Neeraja P. Pillai; Anuvinda P; Sreelekshmi P. J; Devika V; Ramanunni K; Jeevan Sankar R; M.M. Sreejaya (Food Control, 2023)

Confusion assessment method accurately screens for hepatic encephalopathy and predicts short-term mortality in hospitalized patients with cirrhosis - Archita P. Desai; Devika Gandhi; Chenjia Xu; Marwan Ghabril; Lauren Nephew; Kavish R. Patidar; Noll L. Campbell; Naga Chalasani; Malaz Boustani; Eric S. Orman (Metabolic Brain Disease, 2023)

Non-uniform effect of COVID-19 lockdown on the air quality in different local climate zones of the urban region of Kochi, India - George Thomas; Jobin Thomas; Anju V Mathew; R S Devika; Anju Krishnan; Amrutha J Nair (Spatial Information Research, 2023)

Correction: Extracellular Vesicles Derived from a Human Brain Endothelial Cell Line Increase Cellular ATP Levels - Kandarp M. Dave; Wanzhu Zhao; Catherine Hoover; Anisha D’Souza; Devika S Manickam (AAPS PharmSciTech, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Lonar Impact Crater, India: the Best-Preserved Terrestrial Hypervelocity Impact Crater in a Basaltic Terrain as a Potential Global Geopark - Saranya R. Chandran; S. James; J. Aswathi; Devika Padmakumar; R. B. Binoj Kumar; Anil Chavan; Vivek Bhore; Krishna Kajale; Subhash Bhandari; K. S. Sajinkumar (Geoheritage, 2022)

Protein–Protein Interactions on Membrane Surfaces Analysed Using Pull-Downs with Supported Bilayers on Silica Beads - Devika S. Andhare; Himani Khurana; Thomas J. Pucadyil (The Journal of Membrane Biology, 2022)

Assessing the quality of Aeolus wind over a tropical location (10.04 N, 76.9 E) using 205 MHz wind profiler radar - Ajil Kottayil; K Prajwal; M V Devika; S Abhilash; K Satheesan; Roshny Antony; Viju O. John; K Mohanakumar (International Journal of Remote Sensing, 2022)

Development of Lipidoid Nanoparticles for siRNA Delivery to Neural Cells - Purva Khare; Kandarp M. Dave; Yashika S. Kamte; Muthiah A. Manoharan; Lauren A. O’Donnell; Devika S. Manickam (The AAPS Journal, 2021)

Extracellular Vesicles Derived from a Human Brain Endothelial Cell Line Increase Cellular ATP Levels - Kandarp M. Dave; Wanzhu Zhao; Catherine Hoover; Anisha D’Souza; Devika S Manickam (AAPS PharmSciTech, 2021)

DNA Polyplexes of a Phosphorylcholine-Based Zwitterionic Polymer for Gene Delivery - Kandarp M. Dave; Linjiang Han; Meredith A. Jackson; Lindsay Kadlecik; Craig L. Duvall; Devika S Manickam (Pharmaceutical Research, 2020)

Complete mitogenome analysis of endangered Malabar mahseer (Tor malabaricus) - S. Chandhini; V. M. Arjunan; P. H. Anvar Ali; Rajeev Raghavan; Devika Pillai; V. J. Rejish Kumar (Conservation Genetics Resources, 2019)

Effect of dengue mosquito control insecticide thermal fogging on non-target insects - K. G. Thilanka N. Abeyasuriya; N. W. Nalaka P. Nugapola; M. Devika B. Perera; W. A. Inoka P. Karunaratne; S. H. P. Parakrama Karunaratne (International Journal of Tropical Insect Science, 2017)

Molecular characterization of phytoplasma associated with phyllody of Pedalium murex - a common weed in coconut plantations - Merin Babu; A. Josephrajkumar; M. Rajumon; S. Devika; G. Rajeev; K. P. Gangaraj; Vinayaka Hegde (Phytoparasitica, 2015)

Association of Inflammatory Cytokines, Lipid Peroxidation End Products and Nitric Oxide with the Clinical Severity and Fetal Outcome in Preeclampsia in Indian Women - Devika Tayal; Binita Goswami; S. K. Patra; Reva Tripathi; Alka Khaneja (Indian Journal of Clinical Biochemistry, 2014)

Prevalence and breeding habitats of the dengue vectors Aedes aegypti and Aedes albopictus (Diptera: Culicidae) in the semi-urban areas of two different climatic zones in Sri Lanka - Thilini C. Weeraratne; M. Devika B. Perera; M. A. C. Mohamed Mansoor; S. H. P. Parakrama Karunaratne (International Journal of Tropical Insect Science, 2013)

Biochemical markers of liver and kidney function are influenced by thyroid function-a case-controlled follow up study in Indian hypothyroid subjects - Sarika Arora; Ranjna Chawla; Devika Tayal; Vinod K. Gupta; Jagdeep S. Sohi; V. Mallika (Indian Journal of Clinical Biochemistry, 2009)